Prevalencia de stephanurus dentatus en cerdos sacrificados en el camal municipal de Pasaje - Neira Cuenca, Paola Jeanneth (2006)
The present investigation was carried out in the Municipal Camal of the Canton Passage, from the 12 June up to August 21 the 2006. This canton this located in the county from El Oro to the South of the Coast Region of Ecuador. The objectives to be developed in this investigation were: To determine the prevalencia of Stephanurus dentatus in pigs sacrificed in the Municipal Camal of Passage. To determine the prevalencia of Stephanurus dentatus according to the age, race, type of exploitation and origin of the animals. The method used was the one from Daily Direct Inspection to all the pigs faenados; being carried out longitudinal courts in the kidneys, dividing them for the half, in order to discovering cysts or parasitic nodules or the same parasite, likewise he/she was carried out courts in the fatty perirrenal, uréteres, bladder, was inspected it was also observed hepatic lesions due to the migration of the Stephanurus dentatus.. A swinish total of 600 was inspected, of which am a positive case to Stephanurus dentatus, giving us a prevalencia of 0,16%, this positive case was given in a pig less than 12 months of age, type of homemade exploitation, of Creole race and it belonged to the Place Casacay of Passage.